Conceptual subordination in the oral retelling of Spanish-speaking children - Alvarado, Carola; Crespo, Nina; Alfaro-Faccio, Pedro; Silva, María Luisa (Frontiers in Communication, 2024)
Although retelling as a technique to assess narration has been widely used, the input modality seems to impact in different ways on the elicited text, generating a debate about the biases that may appear. To contribute to this discussion, the objective of this study is to describe the development of conceptual subordination and its forms of coding in the oral stories of Spanish-speaking children as well as its relationship with the source text. The stories of 28 five-year-old Chilean school children collected through a retelling task were studied. The analysis consisted of firstly assessing the production of conceptual subordination through the identification of asymmetric links between states of affairs. Then, the encoding forms that instantiated these links were classified. Finally, indices were constructed and applied to compare the children's texts with the source text. During the comparative analysis with the input, three qualitative categories emerged: similar production, reformulation and new link. The results showed that the participants' stories present significantly less production of conceptual subordination link than the source text. However, the children were able to create new links that were not presented in the story and reformulated others, as evidence of an interpretive process that goes beyond the mere reproduction of the input in these types of tasks. Regarding the encoding forms, the results were very similar between the source text and the children's text without significant differences. Both in source texts and children's texts, the prototypical forms of Spanish dominated, allowing us to conclude a possible input bias.